Psychophysiological interventions in biathlon - Wimshurst, Z.; Mosley, E.; Tibbert, S.; Heritage, P.; Neil, G. (BASES Conference 2024, 2024)
Biathlon places a huge demand on psychophysiological processes (Josefsson et al., 2021) yet there is limited research to investigate these. This study aimed to investigate the effect of brief educational interventions based around quiet eye and heart rate variability on shooting performance. Nine international biathletes took part in a cross-over design study where shooting performance was measured at baseline and post intervention. During shooting testing participants had their heartrate variability and gaze behaviour measured. For the inter vention participants undertook educational workshops in quiet eye and slow-paced breathing. Participants also completed workbooks to provide information on their knowledge of each topic pre- and post-intervention, this was rated on a Likert scale from "1" none at all to "7" excellent. Following testing, partici pants took part in focus groups to gain insight into their experi ences. Thematic analysis of focus groups while Mann Whitney U and Wilcoxon Signed Rank tests were used to analyse quantitative data. Results show that the interventions significantly improved shooting performance (Z = 2.34, p = 0.02). Given the small sample size and missing data, there should be caution around the interpretation of shooting improvement. Prior to the workshops participants had very little knowledge of the interventions (quiet eye = 1, slow paced breathing = 1.7) and following the workshops this significantly increased (p < 0.05) (quiet eye = 4.5, slow paced breathing = 5). Participants reported positive responses to the interventions via the focus groups. For example, participants reported the quiet-eye technique helped them to have more control over their gaze behaviour and the paced breathing helped to reduce distractions and increase relaxation. There were some reported barriers to using the interventions such as difficulty associated with chan ging existing routines, interventions conflicting with coaching advice and general scepticism. Overall, there were positive influ ences on both shooting performance and psychological state as a result of both interventions. The findings, specifically those from the workshops and focus groups, suggest that further education for athletes into the psychophysiological factors which may underpin shooting performance is greatly needed.